Carbon‐Neutral Pathways for the United States. Issue 1 (14th January 2021) - Williams, James H.; Jones, Ryan A.; Haley, Ben; Kwok, Gabe; Hargreaves, Jeremy; Farbes, Jamil; Torn, Margaret S.
Abstract: The Intergovernmental Panel on Climate Change (IPCC) Special Report on Global Warming of 1.5°C points to the need for carbon neutrality by mid‐century. Achieving this in the United States in only 30 years will be challenging, and practical pathways detailing the technologies, infrastructure, costs, and tradeoffs involved are needed. Modeling the entire U.S. energy and industrial system with new analysis tools that capture synergies not represented in sector‐specific or integrated assessment models, we created multiple pathways to net zero and net negative CO2 emissions by 2050. They met all forecast U.S. energy needs at a net cost of 0.2–1.2% of GDP in 2050, using only commercial or near‐commercial technologies, and requiring no early retirement of existing infrastructure. Pathways with constraints on consumer behavior, land use, biomass use, and technology choices (e.g., no nuclear) met the target but at higher cost. All pathways employed four basic strategies: energy efficiency, decarbonized electricity, electrification, and carbon capture. Least‐cost pathways were based on >80% wind and solar electricity plus thermal generation for reliability. A 100% renewable primary energy system was feasible but had higher cost and land use. We found multiple feasible options for supplying low‐carbon fuels for non‐electrifiable end uses in industry, freight, and aviation, which were not required in bulk until after 2035. In the next decade, the actions required in all pathways were similar: expand renewable capacity 3.5 fold, retire coal, maintain existing gas generating capacity, and increase electric vehicle and heat pump sales to >50% of market share. This study provides a playbook for carbon neutrality policy with concrete near‐term priorities. Plain Language Summary: We created multiple blueprints for the United States to reach zero or negative CO2 emissions from the energy system by 2050 to avoid the most damaging impacts of climate change. By methodically increasing energy efficiency, switching to electric technologies, utilizing clean electricity (especially wind and solar power), and deploying a small amount of carbon capture technology, the United States can reach zero emissions without requiring changes to behavior. Cost is about 1 per person per day, not counting climate benefits; this is significantly less than estimates from a few years ago because of recent technology progress. Models with more detail than used in the past revealed unexpected synergies, counterintuitive results, and tradeoffs. The lowest‐cost electricity systems get >80% of energy from wind and solar power but need other resources to provide reliable service. Eliminating fossil fuel use altogether is possible but higher cost. Restricting biomass use and land for renewables is possible but could require nuclear power to compensate. All blueprints for the United States agree on the key tasks for the 2020s: increasing the capacity of wind and solar power by 3.5 times, retiring coal plants, and increasing electric vehicle and electric heat pump sales to >50% of market share. Key Points: The United States can reach zero net CO2 emissions from energy and industry in 2050 at a net cost of 0.2–1.2% of GDP, not counting climate benefits Multiple feasible pathways exist, all based on energy efficiency, clean electricity, electrification, and carbon capture for use or storage Least‐cost electricity systems obtain >80% of their energy from wind and solar, with existing types of thermal generation for reliability